PENGARUH TATA KELOLA PERUSAHAAN, STRUKTUR KEPEMILIKAN, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DI INDONESIA - Vefon Hadamean; Dwi Ratmono (Diponegoro Journal of Accounting, 2019)
This study aims to obtain empirical evidence about the affect of board size, proportion of independend board, intensity of meeting, institution ownership, managerial ownership, and  profitability to dividend policy in Indonesia companies. Dividend policy measured by using dividend yield. The population in this study is a company listed on the Indonesia Stock Exchange as an open company. It consists companies in all sectors which pay the dividend during 2015-2017. The amount of the sample used in this study were 387 sample. Data were analyzed using descriptive statistical analysis, multiple linear analysis by Newey-West method, classical assumption test and hypothesis test. The results of the analysis show that board size have a negative and significant effect on dividend yield. Corporate govenance such as proportion of independend board and intensity of meeting have no significant effect on dividend policy. Ownership structure such as institution ownership and managerial ownership have no significant effect on dividend policy. Profitability have no significant effect on dividend policy.